2010
DOI: 10.2298/mpns1002086s
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographyin diagnosis of thoracic diseases

Abstract: Ultrasonography is a very useful second line method in diagnosis of chest disease. The advantages of this method include bed, side availability, absence of radiation, and guided aspiration of fluid-filled areas and solid tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
(26 reference statements)
1
2
0
Order By: Relevance
“…More than two-thirds of all patients had loculated effusion with the complex septate echo structure in half of them. This study and literature data confirmed that existence of intrapleural septa may predict a more complicated clinical course [ 6 , 8 10 , 15 20 ]. Our results and reported series show that the smaller number of complications and high success rate of thoracentesis even in complex loculated collections can be explained by the particular choice of the point of puncture in the skin mark-based method and the constant view and following of the needle during the real-time US-guided intervention [ 13 , 14 , 16 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…More than two-thirds of all patients had loculated effusion with the complex septate echo structure in half of them. This study and literature data confirmed that existence of intrapleural septa may predict a more complicated clinical course [ 6 , 8 10 , 15 20 ]. Our results and reported series show that the smaller number of complications and high success rate of thoracentesis even in complex loculated collections can be explained by the particular choice of the point of puncture in the skin mark-based method and the constant view and following of the needle during the real-time US-guided intervention [ 13 , 14 , 16 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Discussionsupporting
confidence: 86%
“…Lower success rate in thoracentesis or drainage without real-time guidance can be simply explained by shifting of both fluid collection and skin mark with a change in the patient's position. During the real-time US-guided procedure, constant monitoring of the aspiration site helps avoiding thick septa or efficient disruption of thinner septa which enables successful fluid aspiration [ 8 14 ]. More than two-thirds of all patients had loculated effusion with the complex septate echo structure in half of them.…”
Section: Discussionmentioning
confidence: 99%
“…In the majority of cases, clinical signs such as cough and radiologic findings including pathologic mass, inflammatory densities, pleural effusion and pneumothorax are nonspecific [45][46][47]. Diagnosis of lung carcinomas and metastases is based on the US criteria applied to adults [48,49]. When distinguishing malignant and benign pulmonary masses, the following options are used: colour (CD), power (PD) and spectral Doppler (Pulsed Wave Doppler) but solely based on US examination it is not possible to distinguish benign and malignant lesions [50].…”
Section: Lung Carcinomas and Metastasesmentioning
confidence: 99%